PERBEDAAN TINGKAT STRES PADA SISWA FULL DAY SCHOOL SDN KAUMAN 1 KOTA MOJOKERTO DAN HALF DAY SCHOOL SDN TANGUNAN KABUPATEN MOJOKERTO - Dr. Henry Sudiyanto, S.Kp.,M.Kes; Devinta Ristriyanti (MEDICA MAJAPAHIT, 2021)
This study aimed to determine the differences in stress levels in full day school and half day school students. This study used a cross sectional design in which the data collection used the validated PSS-10 (Perceived Stress Scale). Of the full day school students of SDN Kauman 1 Mojokerto City, 15 students (76.2%) had moderate stress levels, and 16 students (71.43%) of the half-day school SDN Tangunan Mojokerto Regency had mild stress levels. The data analyzed by using the Wilcoxon test with a p value of 0.001 so it can be concluded that there are differences in stress levels in full day school students of SDN Kauman 1 Mojokerto City and half day school SDN Tangunan Mojokerto Regency. This indicates that there is a difference in stress levels experienced by students where students with the full day school system tend to have higher stress levels than students who go to school with the half day school system